The Use Of Flash Card Media In Improving Science Learning Outcomes In Elementary School Students - Susanti, Arensi; Febrini, Deni; Mukti, Wiji Aziiz Hari (Passikola: Jurnal Pendidikan Dasar & Madrasah Ibtidaiyah, 2025)
This study aims to determine the use of flash card media in improving science learning outcomes of grade IV students at SDN 09 Kepahiang. This study is a quantitative research with a Quasi Experimental design that aims to test the effectiveness of Flash Card media on the science learning outcomes of grade IV students of SDN 09 Kepahiang. The study involved two groups an experimental group using a Flash Card and a control group using conventional learning methods. The sample consisted of 40 students who were selected purposively, 20 students each in grades IV A and IV B. Data was collected through observation, documentation, and tests in the form of pre-test and post-test. The research instrument was in the form of multiple-choice questions that had been tested for validity (21 valid questions out of 25), reliability (coefficient of 0.758), and difficulty level (the majority of questions were classified as easy to moderate). Data analysis began with a prerequisite test in the form of normality (Chi-Square) and homogeneity (F-test) tests, then continued with hypothesis tests using independent sample t-tests. The results of the analysis aimed to determine the significance of the difference in learning outcomes between students who learned using Flash Cards and those who did not. The findings in the study are that the use of Flash Card media is significantly effective in improving the learning outcomes of science subjects for grade IV students. This is shown by an increase in the average posttest score of the experimental class by 37.75 points to 82.25, which is higher than that of the control class which only increased by 28.5 points with an average of 71.75. The t-test showed statistically significant results (t count = 3.441 > t table = 2.021 at 5%), confirming that the difference in learning outcomes between the two classes did not occur by chance. Flash Cards are proven to help students understand abstract and factual concepts of science through attractive visual presentations and the use of keywords that make it easy to remember. In addition, the interactive nature of this media also increases students' active involvement in the learning process. Thus, Flash Cards not only play a role as a tool, but also as an effective learning strategy in improving the quality of science education at the elementary school level.